2016
DOI: 10.1021/acs.biochem.6b00597
|View full text |Cite
|
Sign up to set email alerts
|

Redox Behavior of the S-Adenosylmethionine (SAM)-Binding Fe–S Cluster in Methylthiotransferase RimO, toward Understanding Dual SAM Activity

Abstract: RimO, a radical-S-adenosylmethionine (SAM) enzyme, catalyzes the specific C methylthiolation of the D89 residue in the ribosomal S protein. Two intact iron-sulfur clusters and two SAM cofactors both are required for catalysis. By using electron paramagnetic resonance, Mössbauer spectroscopies, and site-directed mutagenesis, we show how two SAM molecules sequentially bind to the unique iron site of the radical-SAM cluster for two distinct chemical reactions in RimO. Our data establish that the two SAM molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Coordination of a [4Fe-4S] cluster by three cysteines and a HS − group has precedents in ( R )-2-Hydroxyisocaproyl-CoA dehydratase (Knauer et al, 2011) and HydG involved in maturation of hydrogenases (Dinis et al, 2015). CW electrochemistry suggested that the clusters have very close redox potentials (−420 mV vs. NHE) in the range typical of other RS enzymes (Pierrel et al, 2003; Molle et al, 2016). Moreover, a detailed EPR and Mössbauer study of RimO conducted in the absence of substrate indicated that addition of SAM to the reduced protein triggers a very fast re-oxidation of the RS cluster and none detectable products resulting from the reductolysis of SAM (Molle et al, 2016).…”
Section: Miab and Rimo Enzymes: Methylthiotransferases (Mttases)mentioning
confidence: 90%
See 3 more Smart Citations
“…Coordination of a [4Fe-4S] cluster by three cysteines and a HS − group has precedents in ( R )-2-Hydroxyisocaproyl-CoA dehydratase (Knauer et al, 2011) and HydG involved in maturation of hydrogenases (Dinis et al, 2015). CW electrochemistry suggested that the clusters have very close redox potentials (−420 mV vs. NHE) in the range typical of other RS enzymes (Pierrel et al, 2003; Molle et al, 2016). Moreover, a detailed EPR and Mössbauer study of RimO conducted in the absence of substrate indicated that addition of SAM to the reduced protein triggers a very fast re-oxidation of the RS cluster and none detectable products resulting from the reductolysis of SAM (Molle et al, 2016).…”
Section: Miab and Rimo Enzymes: Methylthiotransferases (Mttases)mentioning
confidence: 90%
“…CW electrochemistry suggested that the clusters have very close redox potentials (−420 mV vs. NHE) in the range typical of other RS enzymes (Pierrel et al, 2003; Molle et al, 2016). Moreover, a detailed EPR and Mössbauer study of RimO conducted in the absence of substrate indicated that addition of SAM to the reduced protein triggers a very fast re-oxidation of the RS cluster and none detectable products resulting from the reductolysis of SAM (Molle et al, 2016). This event was accompanied on a longer time scale by the methylation of the hydrosulfide ligand bound to the UPF cluster (state C).…”
Section: Miab and Rimo Enzymes: Methylthiotransferases (Mttases)mentioning
confidence: 90%
See 2 more Smart Citations
“…It has been shown that in the catalytic reactions of the methylthioltransferases MiaB and RimO,the methyl group is initially attached to the [4Fe-4S] cluster of the enzymes,a nd exogenous methanethiol can serve as the methyl source in the reaction. [14] However, in an assay with d 3 -SAM, NosN,and the other required components in the presence of methanethiol, unlabeled product was not produced in the reaction. This analysis excludes the possibility that NosN uses as trategy similar to MiaB and RimO in placing the methyl group on the [4Fe-4S] cluster before its transfer to the substrate.…”
Section: Angewandte Chemiementioning
confidence: 99%